Evolution of Covid-19 in diabetic patients in a city in southwestern Bahia (Research, Society and Development, 2021)
This article aims to identify the evolution of Covid-19 in patients with diabetes mellitus in the city of Vitória da Conquista, Bahia, Brazil, in order to detect the correlation between the symptoms presented and the hospitalization of these patients, in addition to evaluating the influence of comorbidities associated with the level of hospitalization. For this, a cross-sectional study of a quantitative nature was carried out. The study data were obtained through the electronic medical record inserted in the monitoring system of Covid-19 in the city of Vitória da Conquista. Since the beginning of the Covid-19 pandemic in march 2020 until the month of august 2021, 1770 cases of people with diabetes mellitus contaminated by SARS-CoV-2 were confirmed in the city. General characteristics such as gender, age, race/color, in addition to symptoms and comorbidities associated with diabetes mellitus, patient outcomes, and whether they were health professionals were analyzed. It was found that although females represent a rate of 55%, male patients have a 1.8 times greater risk of evolving to hospitalization. With regard to the hospitalization rate, it was concluded that it is associated with the presence of other comorbidities and the development of symptoms such as a drop in oxygen saturation and breathing difficulties.